Unraveling localized states in quasi free standing monolayer graphene by means of Density Functional Theory. (April 2018) - Cavallucci, Tommaso; Murata, Yuya; Takamura, Makoto; Hibino, Hiroki; Heun, Stefan; Tozzini, Valentina
Abstract: Quasi free standing monolayer graphene (QFMLG), grown on SiC by Si evaporation from the Si-rich SiC(0001) face and H intercalation, displays irregularities in STM and AFM images appearing as localized features, associated with vacancies in the H layer coverage. Size, shape, concentration, and distribution of these features depend on hydrogenation conditions. In order to understand this phenomenology and possibly control it, we perform a Density Functional Theory study of QFMLG with defects in the H coverage of different size and shape and arranged in different configurations. We show that H vacancies generate localized states with highly specific electronic structure. Based on the comparison of simulated and measured STM images we are able to associate different vacancies of large size (7-13 missing H) to the observed features, unraveling the structural diversity of defects of H coverage in QFMLG. Our study indicates a tendency of single H vacancies to aggregate and to locate on a regular superlattice, providing insight into the kinetics of the hydrogenation process. The energy of the localized states associated with these vacancies depends on their size and shape, showing dependence of the electronic properties on the environmental conditions during the sample production. Graphical abstract: Image 1